Trade and growth in small states : the impact of global trade liberalisation (1998)
Addresses the impact of global trade liberalisation upon the growth prospects of small states. Summarises the principle economic characteristics of small states, to highlight the policy implications of their small size and to review the relationship between their economic structure and their growth performance so as to provide insights into the likely consequences of recent regulatory developments in the multilateral trading enviroment.
Keywords: TRADE LIBERALIZATION